Prevalence and Location of Maxillary Sinus Septum and its Relation to Maxillary Sinusitis - Dhami, Bhageshwar; Shrestha, Priti; Saha, Ankit; Pandey, Nashib; Aryal, Deepa (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Maxillary sinus septum is an anatomical variation in the maxillary sinus. Sinus septum is also an important anatomical structure that complicates sinus lift procedure during dental implant placement. Objectives: To assess the prevalence and location of maxillary sinus septa and its relation to maxillary sinusitis using cone beam computed tomography (CBCT scan). Methods: An analytical cross-sectional study was conducted at the Department of Periodontics and Department of Oral Medicine and Radiology, Kantipur Dental College, Kathmandu, Nepal during July 2019 to June 2020 after ethical clearance. In total, 110 subjects and 220 maxillary sinuses were included in the study for evaluation by convenience sampling. The presence of septa, their location and association with maxillary sinusitis were evaluated. Data was analysed using SPSS software with Statistical level set at P<0.05 for significance. Results: The prevalence of maxillary sinus septa in this study was 54 (49.09%). Statistically significant association was found between sinus septa with maxillary sinusitis (p=0.038) and location of septum in the arch (p=0.001). Conclusion: Presence and distribution of maxillary sinus septa is important in planning sinus surgeries and placement of implant in maxillary posterior region.